Prinsip-Prinsip Metode Dakwah Menurut Al-Quran - Aliyudin, Aliyudin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2010)
Daâwah method is one of dakwah system elements that having the urgent role and strategic for succesing daâwah. Daâwah method always develop and follow situation and condition of period. How ever The Holy Qurâan essentially gave foundation that related to the principles in creating varieties of daâwah method. This principleÂ as revealed on an-Nahl: 125, they are al-Hikmah, al-Mauidzah hasanah and al-Mujadalah Ahsan. Then they are actualized by daâwah practice of Rasulullah SAW.